2012
DOI: 10.1093/europace/eus050
|View full text |Cite
|
Sign up to set email alerts
|

Catheter ablation of ventricular fibrillation triggers and electrical storm

Abstract: Ventricular fibrillation (VF) and electrical storm remain challenging conditions to manage despite the availability of various treatment modalities. Insertion of an implantable cardioverter defibrillator (ICD) remains the gold standard method for lowering the risk of sudden cardiac death in patients deemed to be at greatest risk of ventricular arrhythmias. However, ICDs do not alter the underlying substrate responsible for the arrhythmic events and a significant proportion of patients with ICDs may experience … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 63 publications
(70 reference statements)
0
17
0
Order By: Relevance
“…To date, ES remains a challenging condition to manage despite the availability of various management techniques [18]. Most arrhythmic episodes (86-97%) during ES consist of scar-related monomorphic VT [2,19], which makes it feasible for catheter ablation to control ES.…”
Section: Acute Outcomes Of Es Ablation With Rmn: Efficacy and Safetymentioning
confidence: 99%
“…To date, ES remains a challenging condition to manage despite the availability of various management techniques [18]. Most arrhythmic episodes (86-97%) during ES consist of scar-related monomorphic VT [2,19], which makes it feasible for catheter ablation to control ES.…”
Section: Acute Outcomes Of Es Ablation With Rmn: Efficacy and Safetymentioning
confidence: 99%
“…21,22 Functional block or delayed conduction by rapid firing due to triggered activity, or microreentry arising from a single focus, can lead to chaotic ventricular refractoriness (producing dispersion of refractoriness 23 ) without an organic delayed conduction zone. 24 With up-regulation of the beta-adrenergic receptor system, excessive release of sarcoplasmic reticulum Ca 2þ by phosphorylation of RyR2 and disorganizing ventricular refractoriness initiate polymorphic rapid VT and VF. 25 Second, in our present study, more than 1 focus of VT was identified in the malignant VT group during RFCA sessions.…”
Section: Possible Mechanisms Of Malignant Right Ventricular Ot-vtmentioning
confidence: 99%
“…Several groups have reported successful ablation of Purkinje-related VF post myocardial infarction, as well as in amyloidosis, chronic myocarditis and non-ischemic cardiomyopathy. Unlike cases of structural heart disease in which there is a clear substrate, the role of ablation in idiopathic VF, in which the underlying abnormality may be a genetic condition with more widespread electrical instability, remains undefined [6]. Recurrence rates are reported at around 18% at 2 years [7] and therefore ablation cannot be thought as a cure or substitute for an ICD, although it plays a useful role in controlling electrical storm.…”
Section: Discussionmentioning
confidence: 99%